Radiographic and metabolic evolution of prostate cancer lung metastasis detected by prostate-specific membrane antigen and fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography - Tsakiridis, Theodoros; Bonert, Michael; Zukotynski, Katherine; Anagnostopoulos, Alexander (World Journal of Nuclear Medicine, 2020)
We describe the case of a 75-year-old patient who progressed over a 12-year period from localized to symptomatic metastatic prostate cancer (PrCa) with lung as the sole organ of involvement. In this case, the specific sequence of positron emission tomography (PET)-based next-generation imaging with 18F-sodium fluoride-, 18F-fluoro-2-deoxy-D-glucose-, and 18F-DCFPyL PET/computed tomography and biopsies allowed illustration of the pathway of disease progression from nonglycolytic hormone-sensitive PrCa to glycolytic castrate-resistant PrCa without neuroendocrine features. The observations provide a unique insight into the timelines of anatomical and metabolic progression of metastatic PrCa. They highlight the value of close radiographic surveillance of metastatic PrCa with modern imaging to guide early treatment interventions.
Keywords: Castrate-resistant prostate cancer; 18F-DCFPyL; 18F-fluoro-2-deoxy-D-glucose positron emission tomography; lung metastasis; positron emission tomography/computed tomography; prostate cancer; prostate-specific membrane antigen